Topical piperacillin/tazobactam for recalcitrant pseudomonas aeruginosa keratitiS - Chew, F.L.M.; Soong, T.K.; Shin, H.C.; Samsudin, A.; Visvaraja, S. (Mary Ann Liebert Inc, 2010)
Purpose: To report the treatment of therapy-resistant Pseudomonas aeruginosa keratitis with topical piperacillin/tazobactam. Methods: Retrospective report of 3 cases. Results: Three patients with P. aeruginosa keratitis were unresponsive to various antimicrobials. Resolution of all 3 cases of keratitis occurred upon commencement of topical piperacillin/tazobactam. Conclusion: Therapy-resistant P. aeruginosa keratitis acquired from the community is becoming an increasing problem. Topical piperacillin/tazobactam is an option for the treatment of therapy-resistant P. aeruginosa keratitis.